The increased concentration of macrophage migration inhibitory factor in serum and cerebrospinal fluid of patients with tick-borne encephalitis - Sambor Grygorczuk; Miłosz Parczewski; Renata Świerzbińska; Piotr Czupryna; Anna Moniuszko; Justyna Dunaj; Maciej Kondrusik; Sławomir Pancewicz (Journal of Neuroinflammation, 2017)
Abstract Background Host factors determining the clinical presentation of tick-borne encephalitis (TBE) are not fully elucidated. The peripheral inflammatory response to TBE virus is hypothesized to facilitate its entry into central nervous system by disrupting the blood-brain barrier with the involvement of a signaling route including Toll-like receptor 3 (TLR3) and pro-inflammatory cytokines macrophage migration inhibitory factor (MIF), tumor necrosis factor-α (TNFα), and interleukin-1 beta (IL-1β). Methods Concentrations of MIF, TNFα, and IL-1β were measured with commercial ELISA in serum and cerebrospinal fluid (CSF) from 36 hospitalized TBE patients, 7 patients with non-TBE meningitis, and 6 controls. The CSF albumin quotient (AQ) was used as a marker of blood-brain barrier permeability. Single nucleotide polymorphisms rs3775291, rs5743305 (associated with TLR3 expression), and rs755622 (associated with MIF expression) were assessed in blood samples from 108 TBE patients and 72 non-TBE controls. The data were analyzed with non-parametric tests, and p < 0.05 was considered significant. Results The median serum and CSF concentrations of MIF and IL-1β were significantly increased in TBE group compared to controls. MIF concentration in serum tended to correlate with AQ in TBE, but not in non-TBE meningitis. The serum concentration of TNFα was increased in TBE patients bearing a high-expression TLR3 rs5743305 TT genotype, which also associated with the increased risk of TBE. The low-expression rs3775291 TLR3 genotype TT associated with a prolonged increase of CSF protein concentration. The high-expression MIF rs755622 genotype CC tended to correlate with an increased risk of TBE, and within TBE group, it was associated with a mild presentation. Conclusions The results point to the signaling route involving TLR3, MIF, and TNFα being active in TBE virus infection and contributing to the risk of an overt neuroinvasive disease. The same factors may play a protective role intrathecally contributing to the milder course of neuroinfection. This suggests that the individual variability of the risk and clinical presentation of TBE might be traced to the variable peripheral and intrathecal expression of the mediators of the inflammatory response, which in turn associates with the host genetic background.